PSV-3 Comparison of rumen fluid and serum metabolomes in Black Angus cows. - Clemmons, B (J Anim Sci, 2018)
Untargeted metabolomics can provide insight as to the physiological health of an animal; but is currently underutilized in animal systems, particularly with integration of multiple physiological systems. The objective of this study was to determine differences between rumen fluid and serum metabolomes using an untargeted metabolomics approach in order to provide a foundation for future research on rumen function and systemic metabolite utilization. Two fistulated Black Angus cows of approximately six years of age weighing 603.406 ± 37.5 kg were placed on a primarily corn silage-based diet and acclimated to the diet for a two week period. Feed intake was monitored using the GrowSafe system©. Rumen fluid was collected via rumen cannula and blood taken from the coccygeal vein at the beginning of the study and weekly for 12 weeks for a total of 26 samples from each animal. Untargeted serum metabolomics was conducted utilizing the Dionex UltiMate 3000 UPLC system and electrospray ionization was used to introduce the samples into an Exactive Plus Orbitrap MS. A total of 156 known metabolites were identified using MAVEN. Metabolites were median-centered, log-transformed, and range-scaled using Metaboanalyst 4.0. Orthogonal PLSDA showed distinct clustering of serum and rumen fluid metabolites with no overlap (R2Y = 0.987; Q2 = 0.952) with 1000 permutations. A total of 143 metabolites differed between serum and rumen fluid as analyzed by t-test with Benjamini-Hochberg FDR (P ≤ 0.05). The greatest fold metabolite differences (rumen fluid/serum) included 3-methylphenylacetic acid (66.1; P < 0.0001), kynurenine (44.2; P < 0.0001), kynurenic acid (86.2; P < 0.0001), indole (0.0146; P < 0.0001), and cholesterol sulfate (0.00156; P < 0.0001). These data provide evidence of metabolite disparity between blood and rumen content. Further studies may use this information and techniques to account for physiological differences in animals that may contribute to production-important phenotypes.